Non-conventional techniques for management of Aspergillus flavus aflatoxins and preservation of rice grain quality during storage - GUPTA*, ANUJA (Indian Phytopathology, 2010)
Antifungal efficacy of non-conventional and safe treatments were evaluated against aflatoxin producing fungusÂ Aspergillus flavus using bioassay and as dressings during storage for different types of rice grains. The radial growth of theÂ fungus Aspergillus flavus was restricted on PDA medium with increasing concentration of different treatments viz., turmeric,Â cloves and potassium sorbate using food poison technique. Turmeric treatment @ 0.1% (dry seed dressing) gave 43 per centcontrol followed by 36 and 27 per cent control in potassium sorbate and clove treatments, respectively. At 0.4% concentration,Â clove treatment gave 100 per cent control of A. flavus followed by 53 and 51 per cent control in potassium sorbate and turmericÂ treatments, respectively. Exposure to microwave heat for 2 min at 100% power retained the moisture content of grains andÂ inhibited more than 50% fungal growth without adversely affecting the cooking quality of rice grains. The cooking quality ofÂ stored rice grains also remained unaffected irrespective of different treatments and storage conditions even after 15 monthsÂ of storage. The occurrence of fungi including A. flavus increased during successive storage irrespective of the rice types up toÂ 12 months of storage. High fungal incidence was recorded in unpolished rice grain (51.5%) followed by polished rice grainÂ (43.0%) and whole paddy grain (5.5%). Amongst the storage conditions, 20.1% and 13.1% incidence of A. flavus was recordedÂ on grains stored under godown conditions at a rice mill and those stored in the scientific seed stores, respectively. FungalÂ incidences of 20.4% and 12.8% were found associated with grains stored in jute bags and polylined jute bags, respectively.Â Treatment with potassium sorbate, turmeric, cloves and microwave heat exhibited 67.3, 62.7, 37.3, and 5.9 percent control of A.Â flavus, respectively during storage for 15 months under ambient conditions.